INSTITUTIONAL FACTORS INFLUENCING THE IMPLEMENTATION OF HUMAN RESOURCE INFORMATION SYSTEMS IN MACHAKOS COUNTY GOVERNMENT, KENYA - Mutiku, Stella Ndunge; Misango, PhD, Dr. Sedina (Journal of Human Resource and Leadership, 2019)
Purpose: The study was to investigate the institutional factors influencing the implementation of the Human Resource Information System in Machakos County Governments. The study was guided by the four objectives; to explore the influence of leadership style, staff training, change management and organizational policy on the implementation of Human Resource Information System in Machakos County. Methodology: The study employed descriptive research design and data was collected using questionnaires. The study targeted 174 employees of Machakos County and a sample of 88 study participants was randomly selected. The data was analyzed using quantitative data analysis techniques with the aid of SPSS version 21. Correlation and regression were carried out to determine the influence of the independent variables on the dependent variable. Results were presented in tables. Findings: The results showed a P-value of 0.038 implying that implementation of HRIS has a significant joint relationship with leadership style, staff training, change management and organizational policy which is significant at 5 percent level of significance. A t-value of 0.058 was established at 0.047 error margin. This shows that the statistics was significant at 95% significance level. Unique contribution to theory, practice and policy: The researcher recommends that the County Executive Committee members should be ready to implement Human Resource Information System. This would ensure that the environment is welcoming for the system to fully be incorporated. The study further recommends that, the county leadership should allocate time, training manuals and framework and budget to train people on how to use and leverage the uses of Human Resource Information System, and on how to gain competitive advantage through Human Resource Information System. Change management programs should be put in place to ensure that employees fully adapt to the new technology installed. Clear policies regarding the implementation of the Human Resource Information System should be put in place to ensure smooth adoption and implementation of the system.